Evaluation of Agricultural Sustainable Development Based on Resource Use Efficiency: Empirical Evidence From Zhejiang Province, China - Fu, Linlin; Mao, Xiaobao; Mao, Xiaohong; Wang, Jin (Frontiers in Environmental Science, 2022)
Improving resource use efficiency (RUE) is an effective way to accelerate the realization of “carbon emission peak” and “carbon neutrality.” To perform a thorough analysis of the temporal and spatial variations in Zhejiang’s agricultural sustainable development, the present study adopted the entropy weight TOPSIS method and built a RUE-based evaluation index system for sustainable agriculture. The system covered six evaluation aspects: agricultural resource endowment, the agricultural production and agricultural science and technology levels, and ecological, economic, and social benefits. Based hereon, the present study evaluated the agricultural sustainable development of Zhejiang province from 2013 to 2019, and that of its 11 prefecture-level cities and 25 national agricultural sustainable development pilot demonstration zones in 2019. The results showed that chronologically, Zhejiang made steady progress in its agricultural sustainable development from 2013 to 2019, despite slight fluctuations, and spatially, evident regional disparities were found across its 11 prefecture-level cities and 25 pilot demonstration zones. Moreover, resource use efficiency had a significant impact on agricultural sustainable development. Zhejiang’s practices in the efficient use of cultivated land, water resources, forest resources, agricultural labor force, agricultural material goods, and agricultural science and technology offer valuable references for sustainable agriculture worldwide.